Pseudoaccommodating bifocal intraocular lens implantation in eyes with previous corneal refractive surgery - refractive outcomes: case series of 8 eyes - Freitas,Giuliano de Oliveira (2010)
OBJECTIVE: Accurate intraocular lens power calculation may be a challenging issue in eyes with previous corneal refractive surgery. METHODS: The authors present a series of 8 eyes (4 previously submitted to hyperopic laser in situ keratomileusis and 4 to radial keratectomy) submitted to phacoemulsification and implantation of pseudoaccommodating bifocal intraocular lens. Double-K SRK/T formula has been used. RESULTS: Acceptable refractive visual outcomes have been achieved. CONCLUSION: Pseudoaccommodating bifocal intraocular lenses can be safely implanted in patients with previous corneal refractive surgery.